Structural features of five types of maize starch granule subgroups sorted by flow cytometry. (15th September 2021) - Zhong, Yuyue; Li, Yibo; Qu, Jianzhou; Zhang, Xudong; Seytahmetovna, Shayakhmetova Altyn; Blennow, Andreas; Guo, Dongwei
Graphical abstract: Highlights: FC sorts starch granules according to internal structural complexity (ISC) and granular size. ISC was positively correlated with granular size. The subgroup with high ISC had low crystallinity. The subgroup with high ISC had high lamellar ordering. The subgroup with high ISC had the disordered short-range structure. Abstract: Subgroups of starch granules from five maize phenotypes including waxy-, normal-, popcorn-, sweet corn- and high-amylose maize were sorted by flow cytometry (FC) utilizing the side scatter channel (SSC) and forward scatter channel (FSC). SSC and FSC mainly reflecting internal object complexity, and object size, respectively. Subgroups with higher FSC signal always showed higher SSC signal, indicating larger granules exhibited higher internal structural complexity. Wide-angle and small-angle X-ray scattering analysis showed that the subgroups showing high SSC signal intensity also had high lamellar scattering intensity, and low crystallinity. Vibrational transitions of bonds analyzed by Fourier Transform Infrared Spectroscopy (FT-IR) showed that the subgroups of maize starches, except sweet corn starch, with high SSC signal had high intensities at 1045 and 1022 cm −1 . Hence, our data demonstrate that the structural complexity detected by the SSC signal is mainly associated with lamellar and crystalline features of starch granules.